Exploring the effectiveness of the Islamic Spiritual Enhancement Module (ISEM) in reducing stress among university students. - Abdul Khaiyom, Jamilah Hanum; Abdullah Zawawi, Nur Afiqah Izzati; Faris, Waleed Fekry; Bahari, Che Amnah; Abdul Razak, Abdul Latif; Mohamad, Mardiana; Abdullah, Fatimah (2020)
Young adults have been found to be one of the largest age groups that suffer from mental health problems. For the past few decades, literature has found that psycho-spiritual interventions are effective in reducing psychological distress. However, very minimal literature studied its effectiveness on variables such as quality of life and religiosity. The current study aims to explore the effectiveness of a pilot program using a newly developed Islamic Spiritual Enhancement Module (ISEM). A quasi-experimental research design was used. 36 participants given their agreement to participate at the beginning of the intervention but only eight completed the intervention. Measures used in the study comprised of 14-item Stress scale from the Depression Anxiety Stress Scale-42, Perceived Stress Scale-10 item, and 26-item of World Health Organization-Quality of Life-BREF (WHOQoL-BREF), and 10-item IIUM Religiosity Scale (IIUMRelS). 2.5 hour 7-weekly group intervention was conducted with the participants. Results found that there was a significant reduction of stress after the intervention but no significant differences were found in other measures used. Limitations and suggestions for future research were discussed.